György Kurtág: The Sayings of Péter Bornemisza, Op. 7. A 'Concerto' for Soprano and Piano - Willson, Rachel Beckles (Burlington Ashgate, 2004)
Gyorgy Kurtag's The Sayings of Peter Bornemisza op. 7 for soprano and piano (1963-68) is probably the most significant piece of music to have been composed in Hungary since the death of Bartok in 1945. Willson discusses the autobiographical associations at work in the piece, but also its essentially European character.Show More Show Less --------------------------------------------------------------------------------
Keywords: 20th Century (1901-2000); Concerto; Soprano; Piano; Musical analysis; Hungary